Evaluación de fungicida de triazoles y amina en mezclas en el control de Sigatoka negra (Pseudocercospora fijiensis) en banano (Musa paradisiaca - Morales Ortega, Jonathan Benjamín (2022)
Black Sigatoka, caused by the fungus (P. fijiensis), is the main foliar disease of musaceae worldwide. The objective of this research was to evaluate the triazole and amine chemical group fungicides in the control of black Sigatoka in banana cultivation. , using eight treatments of chemical fungicides and a control treatment separated by a living barrier of king grass, using the DCA design with 3 repetitions, experimental unit of 4 plants, the fumigation was carried out with a DJI Agras MG drone. The residuality of the fungicide and the affected leaf area AFA % were evaluated 21 days after application (DAA) at a frequency of 7 days. Statistical differences were observed in leaf 1 and 2 from day 21, up to 56 days when there were differences in the treatments, the lowest averages of AFA% were observed in T6 (Difeconazole + Spiroxamine) with 5.04%, and T8 with 12.92% when applying (Epoxyconazol+ Fenpropimorph) differing from the treatments T1 (Epoxiconazole+Fenpropimorph), T2 (Epoxiconazole+Fenpropidin), T5 (Dicofenazol+Fenpropidin and T9 (Control). The residue evaluated at 63 days DAA in leaf 1 where T2 (Epoxiconazole+Fenpropimorph) with 92.63% in contrast to T9 with 64.00%.In leaf 2 a residuality of 82.83% was observed, reporting statistical differences for T4 (Dicofenazol+Fenpropimorph), T5 (Dicofenaol+Fenpropidin) and T9 , these last treatments reported the lowest percentages of residuality with 67.00, 63.75 and 48.25% Systemic fungicides such as triazoles and amines effectively control the disease, but proper management to avoid resistance of the mushroom.